Calculation method for Mie scattering coefficients by inhomogeneous bianisotropic spherical particle within the operator scattering theory - Novitsky, Andrey V.; Rodriguez, Richard J. Alvarez; Galynsky, Vladimir M. (Journal of the Belarusian State University. Physics, 2018)
Calculation method for the Mie scattering coefficients by inhomogeneous bianisotropic spherical particles is developed. It exploits the scattering fields and integral representation of coefficients. It is shown that within the operator scattering theory the Mie coefficients are expressed by means of the wave impedance tensors in the particle and ambient medium. Using the Mie coefficients determined for the inhomogeneous anisotropic particle we study the existence conditions of directional (predominantly forward) electromagnetic radiation. Generalization of the methodology to the cases of multilayer and cylindrical particles is possible.